Analysis of the surface rupture process of strong earthquakes based on centrifuge tests. Issue 136 (September 2020) - Shen, Chao; Bo, Jingshan; Qi, Wenhao; Zhang, Xuedong; Huang, Jingyi; Qiao, Feng
Abstract: Surface ruptures caused by strong earthquakes are one of the most concerning issues for construction projects. In this paper, geotechnical centrifuge model tests is performed to successfully simulate the reverse faulting process. Using a linear laser displacement sensor (LLDS) and the particle image velocimetry (PIV) technique, the surface deformation process and faulting behaviours are studied in dry and wet sand with a thickness of 40 m above a bedrock surface. Based on an analysis of high-precision surface monitoring data, the soil rupture process is divided into four stages: the overall uplift period, inclination deformation period, scarp growth period, and deformation slowdown and lag period. In addition, the characteristics of the soil deformation and the propagation behaviour of the upper fault tip are obtained. This experiment and related achievements can provide references for further understanding the deformation of thick soil layers caused by reverse faulting. Highlights: The simulated thickness of the overburden soil of reverse fault reached 40 m. The dry sand and wet sand show different surface fracture characteristics. The soil rupture process above the bedrock was divided into four stages. Two fault surfaces eventually present a reverse tilted "✓" shape.